Saving lives through concerts - Abd Razak, Dzulkifli (2005)
If the successes of Live 8 and Group of Eight (G8) summit are anything to go by, one is tempted to conclude that major world problems can be better handled by celebrities and artistes rather than politicians. Already many of them have been made ambassadors to tackle issues and problem like HIV/AIDS, land mines, poverty and even peace on behalf of the United Nations and other international bodies. Bob Geldof and Bono are the two leading examples of such ambassadors that the world has known. It was almost two decades ago that both of them led a host of other singers and musicians to raise money for the Ethiopian famine victims through the Live Aid concert. They manage to attract more than 1.5 billion people in 100 countries live over television, raising awareness about the levels of poverty plaguing humanity, of which Ethiopia was just one of many examples.